A conservative approach in a child with haematuria after accidental rectal impalement trauma - Schijns, Josephine (Afr J Paediatr Surg, 2015)
We present a case of an 11-year-old boy with haematuria after traumatic rectal insertion of a sharp metal stick. It demonstrates that an expectative management with close observation can be considered in patients with rectal impalement trauma presenting with haematuria and stable vital parameters without significant injury on abdominal ultrasound.